2022
DOI: 10.1002/hipo.23414
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relation between hippocampal volume and memory ability in typically developing children and adolescents

Abstract: Memory is supported by a network of brain regions, with the hippocampus serving a critical role in this cognitive process. Previous meta‐analyses on the association between hippocampal structure and memory have largely focused on adults. Multiple studies have since suggested that hippocampal volume is related to memory performance in children and adolescents; however, the strength and direction of this relation varies across reports, and thus, remains unclear. To further understand this brain–behavior relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…First, our results extend previous univariate findings on the relations between brain measures and mnemonic processes in developmental cohorts. For example, studies showed that extended developmental trajectories of hippocampal head ( Botdorf et al, 2022 , Poppenk et al, 2013 ), hippocampal body subfields and EC ( Canada et al, 2019 , Keresztes et al, 2017 ), cerebellar ( Sussman et al, 2016 ), prefrontal ( Bauer et al, 2019 , Botdorf and Riggins, 2018 , Mills et al, 2016 , Mills et al, 2016 , Schlichting and Preston, 2015 , Sousa et al, 2018 , Sowell et al, 2001 ), parietal and occipital ( DeMaster and Ghetti, 2013 , Hebscher et al, 2019 , Himmer et al, 2019 , Karanian and Slotnick, 2015 ) regions are related to age-related differences in encoding and retrieval of memories. The brain profiles identified in our study extend the literature, showing that multivariate profiles comprised of these structural brain measures can also be related to memory retention across short and long delays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our results extend previous univariate findings on the relations between brain measures and mnemonic processes in developmental cohorts. For example, studies showed that extended developmental trajectories of hippocampal head ( Botdorf et al, 2022 , Poppenk et al, 2013 ), hippocampal body subfields and EC ( Canada et al, 2019 , Keresztes et al, 2017 ), cerebellar ( Sussman et al, 2016 ), prefrontal ( Bauer et al, 2019 , Botdorf and Riggins, 2018 , Mills et al, 2016 , Mills et al, 2016 , Schlichting and Preston, 2015 , Sousa et al, 2018 , Sowell et al, 2001 ), parietal and occipital ( DeMaster and Ghetti, 2013 , Hebscher et al, 2019 , Himmer et al, 2019 , Karanian and Slotnick, 2015 ) regions are related to age-related differences in encoding and retrieval of memories. The brain profiles identified in our study extend the literature, showing that multivariate profiles comprised of these structural brain measures can also be related to memory retention across short and long delays.…”
Section: Discussionmentioning
confidence: 99%
“…As our task required both source memory and integration of semantic knowledge to form object-location associations, it may explain the role of hippocampal head in retention of across consolidation. In relation to this subiculum of hippocampal body ( Keresztes et al, 2022 ), CA1 hippocampal body subfields ( Riggins et al, 2018 ), and hippocampal head ( Botdorf et al, 2022 , Riggins et al, 2018 , Schlichting et al, 2017 ) was recently shown to undergo profound volumetric increase in middle childhood, indicating that the age-related increase in structural volume in these regions go hand in hand with improvement in long-delay memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retinal-brain connection revealed in our study posits questions about its implications: can the retinal layers also be related to variations in cognitive performance? Some studies conducted in young people suggested that brain MRI changes may be related to cognitive performance in different domains (Botdorf et al, 2022;Estrada et al, 2019;Lee et al, 2014;Tamnes et al, 2010Tamnes et al, , 2013. However, their cross-sectional design or short-term follow-up preclude drawing conclusions about longer-term cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Other published effects mainly concerned the hippocampus, which was less reflected in our data. Given the function of this structure in the context of memory processing, this is remarkable, as one could possibly assume that brain morphological changes should occur in this region due to, for example, chronic stress experience (Botdorf et al, 2022; Hardcastle et al, 2020; Kim et al, 2015). Examining samples at risk in terms of associations between structural measures and acute stress responses could be a potential prospect at this point (Misaki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%